PENGEMBANGAN SISTEM POINT OF SALE (POS) BERBASIS WEB DALAM MENINGKATKAN COSTUMER RELATIONSHIP MANAGEMENT - Sudirman, Sudirman; Agustina, Ika (Yayasan Education and Social Center, 2024)
The development of technology is growing so fast that there are tools such as very useful applications, no exception in the world of building materials sales business that is increasingly varied for the products sold so in its services must use information technology so that the entrepreneur can provide the best service to its customers as well as facilitate customers in carrying out transactions of purchase of goods. The research of these business issues is an aspect in improving the quality of internal service processes of purchase transactions and also the sale of goods at Centra Buildings of Wealth more efficient, efficient and convenience as well as customer satisfaction in the transaction. The aim of this research is to improve customer trust and good relations through ease, speed in serving customer transactions through the use of Point of Sales (POS) application for ease in recording, data search and data management sales report to consumers systematically and quickly